43 COMPARISON OF BEHAVIORAL PHENOTYPES OF XXY VERSUS XXYY SYNDROME. (1st January 2006) - Davis, S.; Tartaglia, N.; Reynolds, A.; Hansen, R.; Hagerman, R.
Abstract : Purpose of Study: XXY syndrome (Klinefelter's syndrome) is the most common form of sex chromosome aneuploidy in males. Due to a similar physical phenotype, XXYY syndrome has traditionally been classified as a variant of Klinefelter's syndrome. A study directly comparing the cognitive and behavioral features of these two syndromes has not been completed. The purpose of this study is to compare the cognitive and behavioral features of males with XXY syndrome to males with XXYY syndrome. Methods: Patients were recruited from national organizations for patients with sex chromosome aneuploidy. All participants were males between the ages of 2.5 and 20 and had either XXY or XXYY karyotype. All families underwent a clinical interview and parents completed the Behavior Assessment System for Children (BASC). Cognitive testing was obtained using the WASI. Results: The patient groups consisted of XXY males ( n = 15) and XXYY males ( n = 20). There were no significant differences in age between groups (mean age XXY = 9, XXYY = 12). Cognitive measures were compared between groups using t -tests, with statistically significant differences ( p < .05) found in Verbal IQ and Full-Scale IQ but not in Performance IQ (mean VIQ XXY = 100, XXYY = 79; mean PIQ XXY = 100, XXYY = 90; mean FSIQ XXY = 101, XXYY = 83). On the BASC, XXYY males had significantly higher scores in all domains of externalizing behaviors (mean T score externalizing composite XXY =4 9, XXYY = 67). There were also significant differences in Atypicality, Depression, and Adaptive Functioning. There was a negative correlation between Full-Scale IQ and Externalizing Composite in the XXY group but not in the XXYY group (p < .05). Conclusions: XXYY males have Verbal and Full-Scale IQ's significantly lower than males with XXY; however, their performance IQ does not significantly differ. XXYY males are more likely than XXY males to have problems with hyperactivity, aggression, conduct, atypicality, and depression. XXYY males also have significantly lower adaptive functioning than males with XXY syndrome. XXY males with lower IQs are more likely to have externalizing behavior, while IQ does not correlate with externalizing behaviors in XXYY syndrome. Although XXYY syndrome shares some physical features with XXY syndrome, XXYY syndrome appears to have a unique cognitive and behavioral profile and should be distinguished as its own behavioral phenotype.